A mosaic karyotype of 45,X/46,X,psu idic(Y)(q12) in a ten-year-old boy: integrating high-throughput sequencing with cytogenetic technique for precise diagnosis and genetic counselling - Hui Yin; Hua Xie; Jizhen Zou; Xue Ye; Ying Liu; Cai He; Shaofang Shangguan; Haoran Liu; Xiaoli Chen; Xiaobo Chen (BMC, 2023)
Abstract Background Isodicentric Y chromosome (idic(Y)) is the most commonly reported aberration of the human Y chromosome, which is an important cause of abnormal sexual development. The breakpoints of isodicentric Y chromosome mostly occurred in Yq11.2 and Yp11.3, however, the breakpoints in Yq12 are relatively rare. Case presentation We described a 10-year-old boy presenting hypospadias, micropenis and short stature, as well as unilateral cryptorchidism without normal testicular seminiferous tubules structure by biopsy. Whole exome sequencing didn't find any pathogenic/likely pathogenic variants related to phenotypes of this patient. Copy number variation sequencing showed the duplication of whole Y chromosome. Subsequently, karyotyping and FISH analyses demonstrated his genetic diagnosis was mosaic 45,X[8]/46,X,psu idic(Y)(q12)[32], with the breakpoint in Yq12. Conclusions Our case proved that it would be beneficial to integrate high-throughput sequencing with cytogenetic technique for precise diagnosis, treatment and genetic counselling.